NILAI KEARIFAN LOKAL FOLKLOR MASYARAKAT KABUPATEN BINTAN - Tessa, Elfa Oprasmani, Suhardi (Sasando, 2019)
Bintan Regency community has long been known to have various folklore geniuses. But not many have been appointed as objects of research, particularly in terms of the value of their local wisdom. This study used descriptive qualitatative method. Data collection using interview teachniques and documents. Data analysis uses content analysis techniques. The result obtained showed that folklore district of Bintan community contained local wisdom values such as the value of Islamics religion, moral value, social values, hard work values, and educational values.